Understanding the WOM behaviour of e-service users: an empirical study in online travel services. (2016) - Li, Hongxiu; Suomi, Reima
This study proposed a research model to explore the WOM behaviour of e-service users based on the IS post-acceptance model. The research model was empirically tested in the research context of online travel services with data collected in China. The research results indicate that perceived usefulness and user satisfaction affect e-service users' WOM behaviour positively together with trust. Perceived usefulness was found to exert the strongest influence on WOM behaviour followed by satisfaction and trust. The implications for theories and practice are also discussed.